The Goosebump Sign - Wu, Feiran; Ng, Chye Yew (Journal of Hand and Microsurgery, 2019)
Nerve injury may occur following shoulder trauma. However, joint or bony damage can often dominate the clinical picture such that signs of nerve injury are overlooked. We describe the “goosebump sign” as a hitherto undescribed objective clinical finding of sympathetic dysfunction in peripheral nerve palsy, which can be a useful complementary sign to the standard assessment of muscle power and sensibility.
Keywords: peripheral nerve injury; nerve palsy; sympathetic dysfunction; autonomic dysfunction; clinical sign